Supply chain carbon reduction considering consumer skepticism and blockchain technology under the cap-and-trade policy - Peng-peng Yuan; Qingsong Wang (PLoS ONE, 2026)
In the context of low-carbon development, both firms and consumers can contribute to environmental protection. Given that consumers are often skeptical of corporate claims regarding product carbon reductions, this study explores how manufacturers can leverage blockchain technology to invest in carbon abatement under carbon cap-and-trade policies. Then, this study develops three game models within a supply chain involving a manufacturer and a socially responsible retailer to explore firms’ abatement and operational strategies. The model design is based on existing literature as well as real-world corporate practices, cap-and-trade policies, and blockchain transparency mechanisms. The study finds that unit abatement level is negatively correlated with consumer skepticism and positively correlated with the retailer’s corporate social responsibility. When the unit application cost of blockchain is below a certain threshold, manufacturers should adopt blockchain technology to mitigate consumer skepticism, thereby increasing product abatement levels and improving profits. Moreover, this threshold increases with market size and the degree of consumer skepticism. Retailers’ socially responsible behavior can enhance both the manufacturer’s unit abatement level and profitability, while stronger consumer preferences for low-carbon products or higher carbon prices can further motivate retailers to assume social responsibility. When the cost-sharing ratio is at a low level, both firms can achieve a win–win outcome in terms of profitability and environmental performance. The optimal cost-sharing ratio is positively related to the level of consumer low-carbon preference and the level of social responsibility. These findings provide theoretical insights and practical guidance for promoting credible carbon reduction strategies in supply chains.